PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aims to examine how much "Effect of Capital Structure and Profitability on Stock Prices in Food and Beverage Sector Industrial Companies Listed on the Indonesia Stock Exchange". In this study the samples taken were Food and Beverage Sector Industrial Companies Listed on the Indonesia Stock Exchange for the period 2013-2017. The data analysis method used in this study was using multiple regression analysis. The results of the study show that the capital structure and profitability influence the stock price of the Food and Beverage Industry Company Listed on the Indonesia Stock Exchange. It is hoped that this research can be used as a work to add insight into knowledge that can further broaden the mindset of readers, especially regarding the influence of Capital Structure and Profitability on Stock Prices in the Food and Beverage Sector Industrial Companies Listed on the Indonesia Stock Exchange.